Le mouchoir de Vatinius (Quint. Inst. VI, 3, 60) - Zeltchenko, Vsevolod (Hyperboreus, 2021)
The subject of the paper is an exchange between Calvus (the prоsecutor) and Vatinius (the defendant) preserved by Quintilianus (Inst. 6. 3. 60 = Calv. 24 Malcovati) in the section dedicated to the oratorical jokes. Its ﬁrst part deals with the historical context of the dialogue: the popular parallel Inst. 9. 2. 25 (= Calv. 23 Malcovati) has nothing in common with it, since perfricare frontem in 9. 2. 25 is simply a well-known idiom. Meanwhile, Calvus’s invective, extravagant and petty as it is (he attacks Vatinius for wiping his forehead with a white handkerchief which violated the mourning dress code of the defendant), seems justiﬁed if it subtly hints at the events of 59 BC, when Vatinius had deliberately appeared atratus at the solemn banquet of Quintus Arrius and provoked a scandal. The second part aims to demonstrate that the words sunt quaedam vi similia introducing Vatinius’s joke are not sound, and all the emendations proposed are unsatisfactory; Quintilian probably wrote sunt quaedam verbis similia.